The novel capsazepine analog, CIDD‐99, significantly inhibits oral squamous cell carcinoma in vivo through a TRPV1‐independent induction of ER stress, mitochondrial dysfunction, and apoptosis. (4th April 2019) - De La Chapa, Jorge J.; Singha, Prajjal K.; Self, Kristen K.; Sallaway, McKay L.; McHardy, Stanton F.; Hart, Matthew J.; McGuff, Howard Stan; Valdez, Matthew C.; Ruiz, Francisco; Polusani, Srikanth R.; Gonzales, Cara B.
Abstract : Background: Oral squamous cell carcinoma (OSCC) is a deadly disease with a mere 40% five‐year survival rate for patients with advanced disease. Previously, we discovered that capsazepine (CPZ), a transient receptor potential channel, Vanilloid subtype 1 (TRPV1) antagonist, has significant anti‐tumor effects against OSCC via a unique mechanism‐of‐action that is independent of TRPV1. Thus, we developed novel CPZ analogs with more potent anti‐proliferative effects (CIDD‐24, CIDD‐99, and CIDD‐111). Methods: Using OSCC xenograft models, we determined the efficacy of these analogs in vivo. TRPV1 interactions were evaluated using calcium imaging and a rat model of orofacial pain. Anti‐cancer mechanism(s)‐of‐action were assessed by cell cycle analysis and mitochondrial depolarization assays. Results: CIDD‐99 was the most potent analog demonstrating significant anti‐tumor effects in vivo ( P < 0.001). CIDD‐24 was equipotent to the parent compound CPZ, but less potent than CIDD‐99. CIDD‐111 was the least efficacious analog. Calcium imaging studies confirmed that CIDD‐99 neither activates nor inhibits TRPV1 confirming that TRPV1 activity is not involved in its anti‐cancer effects. All analogs induced an S‐phase block, dose‐dependent mitochondrial depolarization, and apoptosis. Histological analyses revealed increased apoptosis and reduced cell proliferation in tumors treated with these analogs. Importantly, CIDD‐99 had the most dramatic anti‐tumor effects with 85% of tumors resolving leaving only minute traces of viable tissue. Additionally, CIDD‐99 was non‐noxious and demonstrated no observable adverse reactions Conclusion: This study describes a novel, highly efficacious, CPZ analog, CIDD‐99, with dramatic anti‐tumor effects against OSCC that may be efficacious as a lone therapy or in combination with standard therapies.